Faktor-Faktor Yang Mempengaruhi Tax Avoidance Perusahaan Manufaktur Yang Terdaftar Di BEI - Jose Juventius Tanamal, Augustpaosa Nariman (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
This research were done with a purpose to empirically examine the influence of profitability (ROA), leverage (DER), firm size dan sales growth toward tax avoidance. This research uses data which collected from secondary data obtained directly from Indonesia Stock Exchange (IDX) official website. Population of this research is industry companies listed on Indonesia Stock Exchange (IDX) for the period of 2017-2019. As much as 81 companies listed on Indonesia Stock Exchange (IDX) are selected as samples in this research based on few criteria. These samples are collected using purposive sampling method. The method that is used on this research was multiple linear regression using Eviews 11 (student version) as test equipment. The result of this research indicate that profitability (ROA) has a negative and significanct effect on tax avoidance, leverage (DER) has a positive and significant effect on tax avoidance, firm size has a negative and significant effect on tax avoidance and sales growth has a negative and significant effect on tax avoidance.